Nigeria-US relations: Diplomacy by the bandwidth (2006)
The concept of information and Communication Technology (ICT) is daily redefining relationships between and among individuals and corporate bodies including nations. As tangible tools, their convergence and application is daily impacting on society so much so that the notion of distance, time and physical barriers has assumed relative virtual meanings in terms of the existence of ICT infrastructures and capacity to utilize the technologies for development by nations. Against this background, attempt is made to discuss how Nigeria and the US can leverage the opportunities presented by technologies to foster their relationship in the 21st century in the context of the two nations’ mutual and disparate strategic interests. It was posited that international relation as art is compatible or amenable technology utilization.In the context of Nigeira-US relationship, it was further posited that security is one area in which the two countries can apply technology provided the challenges of mutual trust, integrity of electronic transactions and availability of bandwidth are addressed. The importance mutual respect for one another as a platform for consensual agreements on issues of common interests, and delicate balancing of divergent strategic national interest was highlighted